2021
DOI: 10.3390/su13168769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute-Partial Sleep Deprivation on High-Intensity Exercise Performance and Cardiac Autonomic Activity in Healthy Adolescents

Abstract: Performing high-intensity exercise (HIE) in the morning under sleep deprivation may harm the health benefits related to sufficient sleep and HIE. Therefore, the aim of this study was to explore the effects of acute-partial sleep deprivation on HIE performance and cardiac autonomic activity by monitoring heart rate variability (HRV) indices. Twenty-nine healthy male adolescents in college were recruited to perform a one-time HIE session on the treadmill (Bruce protocol) after ≥7 h of normal control sleep (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Estrogens and chromosomes are likely to have diverse effects on BP control mechanisms (Maranon and Reckelhoff, 2013). However, in a CONSORT study by Zhang et al (2021), healthy participants with sleep deprivation had lower cardiac vagal activity, as evidenced by lower RMSSD, high-frequency power in normalized units, SD1, and pNN50 values, than those without sleep deprivation. Furthermore, Li et al (2019) reported that those who slept for less than 7 h per day had a higher risk of hypertension than individuals who slept 7-8 h per day in a large-scale study (19,407 adults aged 18-79 years).…”
Section: Hrv Hr and Bp Variablesmentioning
confidence: 99%
“…Estrogens and chromosomes are likely to have diverse effects on BP control mechanisms (Maranon and Reckelhoff, 2013). However, in a CONSORT study by Zhang et al (2021), healthy participants with sleep deprivation had lower cardiac vagal activity, as evidenced by lower RMSSD, high-frequency power in normalized units, SD1, and pNN50 values, than those without sleep deprivation. Furthermore, Li et al (2019) reported that those who slept for less than 7 h per day had a higher risk of hypertension than individuals who slept 7-8 h per day in a large-scale study (19,407 adults aged 18-79 years).…”
Section: Hrv Hr and Bp Variablesmentioning
confidence: 99%
“…25 Research conducted in China in 2021 shows that partial sleep deprivation decreases cardiac vague activity and thus increases the heart rate. 26 Through sympathetic over activity, sympathovagal imbalance, and arterial baroreflex, lack of sleep also raises blood pressure. 27 In addition, dietary consumption and insufficient sleep both contribute to hormone abnormalities.…”
Section: Sleep Disorders and Its Mechanisms Impact On Cardiovascular ...mentioning
confidence: 99%